The meaning of African Traditional Religion for modern society: Zimbabwe as a case study - Humbe, Bernard Pindukai (University of the Free State, 2020)
In contemporary times, religion has dominated the African studies. This study is an effort to contribute to the theme of the meaning of religion in African context. Basing on fieldwork in Buhera District, this work provided a qualitative interpretive study of the meaning of African Traditional Religion (ATR) in modern society of Zimbabwe. Afrocentrism and Symbolic Interactionism were the two theoretical frameworks found to be ideal for this study. Using a phenomenological approach, interviews and observations, the research took the functional, substantive and affective meanings as the modus operandi in the postulation of the meaning of African traditional religious practices in Zimbabwe. It challenges in a special way the idea of fashioning the meaning of ATR pre-occupied with the indigenous Supreme Being-talk, but also with the praxis of ATR in the modern human society. Inadequacy of studying ATR in the modern society of Zimbabwe with foreign nomenclatures was highlighted since English monikers like ATR are hardly used by the Shona people in their daily language. Rather, they commonly use Chivanhu, a vernacular term which is closely equivalent to religion. The thesis creates an awareness to discover rich values of Shona cultural values and belief systems and their place in the meaning of ATR. So in this study ATR and Chivanhu are used interchangeably. During the study, it was noted that there are various matrices of forces that determine the meanings of ATR in the modern society of Zimbabwe, which include: transcendental power, architectural power, traditional power, family power and modernity power. Whether the meaning of ATR is substantivist, affective or functionalist, it was found to be never entirely neutral and objective for it holds various hidden assumptions. Sometimes the meanings attached to ATR in the modern society are ideological or tactical designations. In a bid to search for its meaning, it has proved to be debatable whether ATR is essentially a private and individual matter or fundamentally communal and national. In a Zimbabwean multi-religious society, the issue of the meaning of ATR has been characterised by some problems especially when it gives in to the dictates of the country‘s constitution to avoid clashes. The profundity of the emancipation of women in the modern society has also contributed towards a gendered outlook of ATR in modern Zimbabwe. These kind of imports are often explanations advanced in support of an overriding view of traditional religion, summarised in aphorisms and or epigrams such as: Chivanhu chedu chinoti (our Chivanhu says) ichi ndicho Chivanhu chedu (this is our Chivanhu), musha mukadzi (the key person in a home is a woman). Thus the use of clichés in modern society has impacted the meaning of ATR in Zimbabwe. To this end, the conceptualisation of ATR in modern society of Zimbabwe is characterised by dynamics of alterisation processes that condition the contemplation between this religion and western religions (especially Christianity). These processes of alterisation are characterised by representing and treating ATR through synecdochisation, exoticisation, undervaluation, overvaluation, misunderstanding and exclusion. Though use of a substantivist, affective and functionalist perspective was handy in construing the meanings of ATR in the modern society of Zimbabwe, the same schemes of meaning for religion in various ways explained away ATR.
Keywords: Thesis (Ph.D. (Religion Studies))--University of the Free State, 2020; African Traditional Religion; Zimbabwe -- African Traditional Religion; Afrocentrism; Chivanhu